Telaah Kritis atas Pemikiran Ekonomi Islam Abdul Mannan - Fahrur Ulum (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2009)
This article analyses the opinion of Abdul Mannan on certain main aspects of Islamic economy. They are the scope of Islamic economy, its several basic assumptions, its characteristics and its institutional framework. In his endeavor to construct the science of Islamic economy, like other Islamic economists, Abdul Mannan determines simple basic economic functions which cover three functions; consumption, production, and distribution. A person’s consumption attitude is influenced by his/her needs. Abdul Mannan then divides human needs into three categories; necessities, comforts dan luxuries.In relation to prduction aspect, production system of an Islamic state must stand on objective criteria which is measurable in form of material welfare, and subjective one which is attainable in the light of shari’a. Meanwhile, in the aspect of distribution of income and wealth, there are some proposed policies to prevent the concentration of wealth in a certain group of people through the enactment of duties justified with Islamic law and those of voluntary distribution. Mannan’s opinions are admittedly fresh ideas, but there are some ambiguities open to critiques.